Teachers' Content Knowledge, Beliefs, and Practice after a Project-Based Professional Development Program with Ultrasound Scanning. Issue 3 (2nd April 2020) - Lotter, Christine; Carnes, Nathan; Marshall, Jeff C.; Hoppmann, Richard; Kiernan, Daniel A.; Barth, Steven G.; Smith, Christina
ABSTRACT: This research investigated 20 middle and high school teachers' use of project-based learning curriculum after engaging in a 115-hour professional development program that was developed collaboratively with medical school and education faculty. The project-based learning (PBL) unit centered on the case of Marcus Brown (a pseudonym), a high school football player, who collapsed suddenly while playing football. The teachers engaged in scientific investigations, including ultrasound investigations of standard patients' internal anatomy, and research into various inherited cardiovascular diseases to determine a final diagnosis for Marcus. The teachers, using this PBL as a model, developed and taught their own project-based learning unit to their students during the following year. Through pre and post-program interviews, classroom observations, and content assessments, our results show that the teachers improved their content knowledge and quality of inquiry-based instruction over the program. The teachers also modified their instructional beliefs to align with more reform-based beliefs about student learning and teaching. Our analysis of teacher interviews provides insights into the elements of PBL instruction that teachers struggle with implementing. This study also provides insight into the value of using ultrasound scanning technology with K-12 teachers and students. These findings can improve professional development targeting the integration of NGSS scientific and engineering practices and disciplinary core ideas (content).